A novel low-resistance damper for use within a ventilation and air conditioning system based on the control of energy dissipation. (15th June 2019) - Gao, Ran; Wen, Shihao; Li, Angui; Zhang, Hengchun; Du, Wuyi; Deng, Baoshun
Abstract: Within the central air conditioning systems in public buildings, the energy consumption of fans induced by duct resistance accounts for 30%–50% of the total energy consumption of the buildings. Reducing the resistance within ventilation and air conditioning system is thus an important technical problem. In this research, a novel low-resistance damper, the shape of which based on the energy dissipation characteristics, was introduced for use in a ventilation and air conditioning system. The resistance characteristics were analyzed, the resistance field (the distribution of the resistance at various locations inside the component) was described through the energy dissipation, and a full-scale experiment was carried out to verify the performance of the novel damper. The novel air damper exhibited less fluid deformation, lower intensity, smaller airflow vortex range, and less conversion of mechanical energy into internal energy, which significantly reduced the energy dissipation. Under different air velocities (3–12 m/s), the novel air damper was far more efficient at reducing the resistance than the single-leaf damper with a local resistance reduction rate of 81.4%∼87.16%. Highlights: A low-resistance duct damper was introduced. Energy dissipation was used to describe the "resistance field". The local resistance reduction rate is within 81.4%∼87.16%.